Modulated Electrohyperthermia in Integrative Cancer Treatment for Relapsed Malignant Glioblastoma and Astrocytoma: Retrospective Multicenter Controlled Study. (February 2019) - Fiorentini, Giammaria; Sarti, Donatella; Milandri, Carlo; Dentico, Patrizia; Mambrini, Andrea; Fiorentini, Caterina; Mattioli, Gianmaria; Casadei, Virginia; Guadagni, Stefano
Background: There are interesting studies on glioma therapy with modulated electrohyperthermia (mEHT), which combines heat therapy with an electric field. Clinical researchers not only found the mEHT method feasible for palliation but also reported evidence of therapeutic response.Purpose: To study the efficacy and safety of mEHT for the treatment of relapsed malignant glioma and astrocytoma versus best supportive care (BSC).Methods: We collected data retrospectively on 149 patients affected by malignant glioma and astrocytoma. Inclusion criteria were informed consent signed; >18 years old; histological diagnosis of malignant glioma or astrocytoma; relapsed after surgery, adjuvant temozolomide-based chemotherapy, and radiotherapy; and indication for treatment with mEHT in palliative setting. mEHT was performed with capacitive coupling technique keeping the skin surface at 26°C and the tumor temperature at 40°C to 42.5°C for > 90% of treatment duration (20-60 minutes). The applied power was 40 to 150 W using a step-up heating protocol. Results from patients treated with mEHT were compared with those treated with BSC.Results: A total of 149 consecutive patients were enrolled in the study, 111 (74%) had glioblastoma multiforme (GBM), and 38 (26%) had astrocytoma (AST). mEHT was performed for 28 (25%) of GBM and 24 (63%) of AST patients. Tumor response at the 3-month follow-up was observed in 29% and 48% of GBM and AST patients after mEHT, and in 4% and 10% of GBM and AST patients after BSC, respectively. The survival rate at first and second year in the mEHT group was 77.3% and 40.9% for AST, and 61% and 29% for GBM, respectively. The 5-year overall survival of AST was 83% after mEHT versus 25% after BSC and 3.5% after mEHT versus 1.2% after BSC for GBM. The median overall survival of mEHT was 14 months (range 2-108 months) for GBM and 16.5 months (range 3-156 months) for the AST group. We observed 4 long-term survivors in the AST and 2 in the GBM group. Two of the long survivors in AST and 1 in GBM group were treated by mEHT.Conclusions: mEHT in integrative therapy may have a promising role in the treatment and palliation of relapsed GBM and AST.